Analisis Hubungan Kualitas Pelayanan, Sumber Daya Manusia dan Mutu Pelayanan dengan Kepuasan Pasien di Puskesmas Maiwa - Muhammad Rahmat Ramadhan Aras; Sunandar Said; Mardhatillah; Khaeriyah Adri (Jurnal Administrasi Politik dan Sosial, 2026)
Patient satisfaction is an important indicator in efforts to improve the quality of health services in health care facilities. Low patient satisfaction rates will impact the development of Community Health Centers. The level of patient satisfaction at Maiwa Community Health Center is not fully optimal even though it has provided services according to applicable standards. This study will be conducted at Maiwa Community Health Center with the aim of analyzing the relationship between service quality, human resource competency and service quality with patient satisfaction at Maiwa Community Health Center. This study uses a quantitative approach using a cross-sectional design with a total population of 99 inpatients and a sampling technique of simple random sampling using the Slovin formula to obtain 79 samples. Data were collected through questionnaires, observations, and interviews, then analyzed using the Chi-square test to see the relationship between variables. The results of the study indicate that there is a relationship between service quality, human resources and service quality with patient satisfaction at Maiwa Community Health Center. Service quality has a significant relationship with patient satisfaction, with a p-value of 0.034 (<0.05). Human Resources also showed a significant relationship, with a p-value of 0.000 (<0.05). Similarly, Service Quality obtained a p-value of 0.022 (<0.05).